Impact of early haemodynamic assessment by echocardiography on organ dysfunction and outcome of patients admitted to the emergency department with sepsis or septic shock: protocol of a multicentre randomised controlled trial (GENESIS) - Bruno Giraudeau; Amélie Le Gouge; Philippe Vignon; Thomas Lafon; Samia Brit (BMJ Open)
Introduction Acute circulatory failure plays a major role in the development of sepsis-related organ dysfunction. Current ‘bundles’ of the Surviving Sepsis Campaign (SSC) include the administration of a fluid loading of 30 mL/kg in the presence of hypotension within the first hour of sepsis identification. The impact of haemodynamic assessment using echocardiography at the early phase of management of septic patients in the Emergency Department (ED) on patient-centred outcomes is unknown.Methods and analysis This is a two-parallel arm randomised trial with blinded assessment comparing early haemodynamic assessment using transthoracic echocardiography aimed at guiding therapeutic management to standard of care according to current SSC recommendations in septic patients during initial management in 13 French EDs. Patients with suspected or documented infection and a qualifying quick Sequential Organ Failure Assessment (qSOFA) score (haemodynamic criterion required: systolic blood pressure≤100 mm Hg) will be 1:1 randomised after 500 mL of fluid loading initiation. In the intervention group, echocardiography will allow identifying the haemodynamic profile at the origin of sepsis-induced circulatory failure and monitoring the efficacy and tolerance of fluid resuscitation, or of any other therapeutic intervention according to a predefined therapeutic algorithm. The control group will receive conventional 30 mL/kg fluid resuscitation (unless pulmonary venous congestion) according to SSC recommendations. Primary outcome will be the course of organ dysfunction assessed by the crude change in the modified SOFA score between baseline and 24 hours after randomisation. Secondary outcomes will be the nature of therapeutic interventions resulting from echocardiography (fluid loading, early initiation of vasopressor support or inotrope), the prevalence of the different haemodynamic profiles, the evolution of lactatemia, the safety of the initial therapeutic, the proportion of patients who develop secondarily septic shock, the orientation of patients after ED discharge and both day 7 and in-hospital mortality. We plan to randomise 312 patients.Ethics and dissemination Approved by the Ethics Committee CPP Ouest V on 18 January 2021 (ref: 20/075-2-20.10.16.57638). The dissemination plan includes presentations at scientific conferences and publication of results in a peer-reviewed journal.Trial registration number NCT04580888.